Forced Marriage as Sexual Violence: An Analytical Study under Indonesian Law and the Shafi’i School of Thought - Nurdiansyah, Putra Pandu Dinata; Jamilah, Jamilah (Suhuf: International Journal of Islamic Studies, 2026)
Background: Family decisions that exceed their rightful authority can lead to forced marriage. Law No. 12 of 2022 significantly amends the legal framework by recognising forced marriage as a form of sexual violence, characterising it as coercion and a violation of individual consent. In contrast, the Indonesian Marriage Law and the Compilation of Islamic Law require both the guardian’s obligation and the bride’s consent for a valid marriage. Objective: This study analyses forced marriage as a criminal offence of sexual violence under Law No. 12 of 2022 and within the Shafi’i school of jurisprudence. Methodology: The research employs normative legal methodology, as well as doctrinal, conceptual, and comparative legal approaches, to examine various legal sources. Results: The Islamic principle of ijbar, which allows a guardian to arrange a marriage for a dependent, has sometimes been misused to justify coercive unions on religious grounds. Conclusion: Indonesian law classifies forced marriage as sexual violence, while Shafi’i jurisprudence regulates ijbar with strict and specific conditions. The findings suggest that increasing public awareness and harmonising religious and state legal frameworks are essential to prevent forced marriages and protect the rights of women and children.